(untitled) - Weissman, Julie (Lincolnwood, 1997)
Updated to reflect the world of to day's consumer, Everyday consumer English, second Edition is designed for those who want to improve their english language skills while developing the consumer skills needed for everyday situations. Each of the eight units presents the essential vocabulary and structures needed for successfully performing day-to-day activities, including,....
Keywords: English language; Study and teaching